Efektivitas Pelayanan Mahasiswa Pada Bagian Akademik Kantor Pusat Unsrat - Assa, Fransisca Pegiyani; Rompas, Sonny; Dengo, Salmin (Sam Ratulangi University, 2015)
Abstract: The purpose of this research is to know the effectiveness of the Ministry on students whohad been given by the officers and employees that are on the honorary academic headquarters unsrat. In theframework of the management of higher education in accordance with the Government Regulation Number49 by 2013 about higher education, on article 11 explains that The Academic has the task of implementingthe service giver education, research and community service. In the framework of the management of highereducation in accordance with the Government Regulation Number 49 by 2013 about higher education, onarticle 11 explains that The Academic has the task of implementing the service giver education, research andcommunity service. So in this case can be in describing how the importance of the academic section at theUniversity of Sam Ratulangi.The research methods used in this research is qualitative, descriptive methods with gatheringtechniques by using the method of Observation and question form. as for the respondents/informants of thisresearch was 5 officers, five honorary degrees, and 10 students. So a Total of 20 people was the informant.The results showed that 50% of student respondents were not satisfied with the Ministry's officersthat there is the Head Office of academic Unsrat. According to this study of student dissatisfaction because ofthe way delivery of employee information on students who are less friendly and does not provide informationthat would be expected by the student convey information, both the study also shows that 50% of studentsrespond less well enough and with payment of tuition fee online because according to observation andresearch is less in case of disruption of students agree the internet is often the current payment of tuition feecan't be done and it is very detrimental for students. The results showed that students are less agree withclosing the online graduation registration 2 weeks before graduation day. Because of the internet studentopinions often have disorders that does impact on the clearance delay graduation by the student file.Referring to the discussion and conclusions on top then suggest employees should be able to provideservice and afford maximum to students because students are the main customers of the University of SamRatulangi. The friendly nature of the staff in providing service to give satisfaction in the student. Accurateinformation can be given to a student in any communication directly between the leadership with employeesfor example 1 Provost Academics should be down directly control and provide the latest information relatingto the existing services in the field of academic excellence in order to provide the information needed by thestudent is not Academic leaders can be expected to provide services manually for the payment of theregistration FEE, graduation and others in order to cope with the loss on students because in these days offrequent disruptions of the internet that could slow down the Affairs of the students ' needs.Keywords: Service, Effectiveness